THE EFFECT OF THE NUMBER OF WINDINGS ON TORQUE AND POWER OF A 250W ELECTRIC MOTOR ON AN ELECTRIC BICYCLE - Dananjoyo, Ajitiyo; Fahrudin, A’rasy (Journal for Technology and Science, 2025)
Objective: This study aims to investigate the effect of variations in the number of windings on torque and power output in a 250 W DC motor applied to electric bicycle propulsion, considering the growing demand for efficient, low-cost, and environmentally friendly ground transportation. Method: An experimental approach was employed by modifying the armature windings of a DC motor through both increasing and decreasing the number of coils. Motor performance was evaluated by measuring rotational speed (RPM), torque, and output power under standard winding conditions, additional windings, and reduced windings. Results: The standard winding configuration produced a torque of 0.55 Nm and power of 5.7 W at 100.4 RPM. Increasing the number of windings resulted in a torque of 0.55 Nm and reduced power of 4 W at 77.8 RPM. Conversely, reducing the windings increased rotational speed to 131.3 RPM, yielding a torque of 5.5 Nm and power of 7.5 W. The findings indicate that increased windings reduce RPM and power, while reduced windings enhance RPM and power output. Novelty: This study provides empirical evidence on how winding modification directly influences DC motor performance in electric bicycles, offering practical insights for optimizing motor design through winding configuration adjustments.